2017
DOI: 10.1002/brb3.682
|View full text |Cite
|
Sign up to set email alerts
|

The treatment methods for post‐stroke visual impairment: A systematic review

Abstract: AimTo provide a systematic overview of interventions for stroke related visual impairments.MethodA systematic review of the literature was conducted including randomized controlled trials, controlled trials, cohort studies, observational studies, systematic reviews, and retrospective medical note reviews. All languages were included and translation obtained. This review covers adult participants (aged 18 years or over) diagnosed with a visual impairment as a direct cause of a stroke. Studies which included mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 176 publications
0
38
0
1
Order By: Relevance
“…Considering the aforementioned visual impairments that stroke patients may have, visual scanning training is a commonly used technique that encourages and guides patients to look in a systematic way to both their left and right sides of their visual field. By constantly looking on their blind side, visual processing problems that are related with difficulties of the brain processing the information received by the eyes should disappear over time [29].…”
mentioning
confidence: 99%
“…Considering the aforementioned visual impairments that stroke patients may have, visual scanning training is a commonly used technique that encourages and guides patients to look in a systematic way to both their left and right sides of their visual field. By constantly looking on their blind side, visual processing problems that are related with difficulties of the brain processing the information received by the eyes should disappear over time [29].…”
mentioning
confidence: 99%
“…This statement is true in the sense that there is no sufficient evidence to support that visual field defects can be restored with rehabilitation [24]. However, appropriate glasses, vision rehabilitation, and personalized information and guidance can improve visual function and adaption to VIs [22,24,34]. Valuable tools and advice on strategies to help adapt to and cope with their VIs were unavailable for participants, and they had the impression that nothing could help them.…”
Section: Visual Problems As a Presenting Symptom Of Strokementioning
confidence: 99%
“…Learning to live with a visual loss is a comprehensive and complex task closely intertwined with existential and social aspects [18][19][20]. Regardless of severity, much can be done to recover from or improve VIs through vision rehabilitation [21,22], even if high quality randomized controlled trial (RCT) studies do not show evidence of effective treatment for visual field loss [23]. Several studies have concluded that identifying and give advice on VIs and coping strategies will raise self-awareness [22], and that visual compensatory training is useful for vision outcomes [23,24], rehabilitation of other consequences of stroke, and the overall rehabilitation process [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two clinically used interventions to improve vision in hemianopia are visual search compensatory training and provision of monocular prisms [9]. These interventions for homonymous hemianopia were evaluated by a Cochrane systematic review and limited evidence was found in favour of visual search training [10].…”
Section: Introductionmentioning
confidence: 99%